Casually demystifying a sinister book: Playing with a bestseller whose content nobody is familiar with. Issue 175 (1st November 2015) - Irmer, Thomas
In the framework of Kunstfest Weimar, Rimini Protokoll staged the premiere of Adolf Hitler: Mein Kampf, Vols. 1 & 2. Seventy years after the author's death, the book's copyright in Germany has expired, which raises the question of how much of a taboo and how dangerous the book still is. This question is also at the centre of the mentioned performance; it was made in cooperation with people connected to the book through personal stories, which sheds light on the book from other perspectives and at the same time demystifies it.